New method of measuring subjective well-being: prospective validation study of the ‘Daily Experience Sampling Questionnaire’ (DESQ) in patients with psoriasis and healthy subjects in Germany - Matthias Augustin; Natalia Kirsten; Ibrahim Nergiz; Ulrich Schiffner; Marina Otten (BMJ Open)
Objectives To validate the newly developed Daily Experience Sampling Questionnaire (DESQ) that measures affective subjective well-being (SWB). The DESQ is an end-of-day diary in which respondents retrospectively rate their SWB at six different, randomly determined moments; it is completed over 1 week. The DESQ shall provide an alternative or complementary approach to existing methods of near-time SWB measurement (experience sampling, Day Reconstruction Method). The primary research objective was to determine criterion validity of the DESQ.Design Prospective, non-interventional study.Setting Participants were recruited in Hamburg, Germany, at a specialised outpatient clinic (patients) and via different channels (healthy participants).Participants 101 adults with diagnosed and stable psoriasis (46 women, 55 men); 105 adults without psoriasis (49 women, 56 men).Primary and secondary outcome measures Participants completed the DESQ for 3 weeks. In weeks 2 and 3, they also performed experience sampling. Criterion validity was determined by weekwise intraclass correlations (ICC) between both methods. Sensitivity to change was determined by the correlation between changes in both methods from weeks 2 to 3. For convergent validity, related concepts such as life satisfaction were measured. Retest reliability was determined using DESQ values of weeks 2 and 3.Results Criterion validity was excellent (ICC: patients=0.86, 95% CI 0.81 to 0.91; healthy participants=0.86, 95% CI 0.79 to 0.91). Sensitivity to change was r=0.57 and r=0.56, respectively. Correlations with convergent criteria were mostly significant and higher in constructs more proximal to SWB. The ICC indicating retest reliability was 0.77 in patients (95% CI 0.68 to 0.84) and 0.81 in healthy participants (95% CI 0.73 to 0.86).Conclusions The DESQ is a valid, reliable and feasible instrument for SWB measurement in people with psoriasis and healthy people. Its approach of end-of-day evaluations of single moments may also lend itself to the measurement of other highly time-variant constructs such as pain, fatigue or depression.